A critical success factors model for IS implementation: Development and validation of a structural model using PLS - Abdullah, Z.; Quaddus, Mohammed (2012)
The delivery of high quality health services is among the most important government policies in healthcare; it is demonstrated via the significant investment committed to expand the sector. In order to provide quality health services, Hospital Information Systems (HIS) development and adoption has to be initiated; though evidence has shown that implementing HIS is not easy. To ensure continuous successful implementation, the understanding and determination of HIS implementation factors has become a crucial consideration for health providers. This study, instigated to alleviate this problem, identified critical factors that influence HIS implementation and examined structured indicators to measure HIS implementation. Conceptually, it extends theory by reframing the critical success factors that influence HIS implementation. Empirically, it confirms that PLS path modelling can be used to estimate the parameters of a higher order construct. Finally, the study concludes by discussing the conceptual contribution and practical implications. © 2012 AICIT.